What next? - Hashim, Haslinda; Mohamat Din, Nurakmalina (Universiti Putra Malaysia Press, 2013)
This case revolves around a pharmaceutical company named Covorex (Malaysia). The head office is Covorex Pharma which originates in Germany. It was founded in 1950 and has grown into a global multinational company with more than 150 subsidiaries worldwide. Covorex (Malaysia) was established as a local subsidiary in 1980 to enable the distribution and marketing of Covorex Pharma pharmaceutical products in Malaysia. It has branches all over the country such as in Ipoh, Kota Bharu, Johor Bharu, Penang, Kuantan, Kuching and Kota Kinabalu, with over 200 employees. This case focuses on the sales performance of Covax, a new product introduced to clients in the Government-Hospital market. The case presents an opportunity for postgraduate and undergraduate students to apply and test their knowledge in Business to Business (B2B) marketing, integrated marketing communication and personal selling topics.